Human mesenchymal stromal cells transplanted into mice stimulate renal tubular cells and enhance mitochondrial function - Luca Perico (Nature Portfolio, 2017)
Mesenchymal stromal cells drive renal regeneration following injury. Here, the authors show that human mesenchymal stromal cells, when transplanted into mice with acute kidney injury, stimulate renal tubular cell growth and enhance mitochondrial function via SIRT3.